SABER-ICT Framework Paper for Policy Analysis : Documenting National Educational Technology Policies Around the World and Their Evolution over Time - Trucano, Michael (World Bank, Washington, DC, 2017)
The systems approach for better education results (SABER) - information and communication technology (ICT) policy framework is designed to help policymakers make better informed decisions about how best to use ICTs in pursuit of core developmental objectives in the education sector. It aims to aid and inspire education policymakers as they draft, re-consider, and evaluate key policies related to the use of ICT, especially within the formal education sector at the primary and secondary (K-12) level. The framework was constructed by analyzing and synthesizing policy documents from over 80 countries. The vast majority of these policies relate to formal schooling at the primary and secondary level; related official policy guidance for other parts of an education system, including at the level of early childhood development, technical, and vocational education (TVET) and higher education, as well as pertain to out-of-school and life-long learning, is comparatively rare. While the SABER-ICT framework was constructed through an analysis of national ICT and education policies, it is expected that it may be useful when attempting to analyze and benchmark related sub-regional policies (that is, at the provincial or state level) as well.